1977
DOI: 10.1121/1.381579
|View full text |Cite
|
Sign up to set email alerts
|

Electronic models to simulate the effect of sensory distortions on speech perception by the deaf

Abstract: Electronic models that process signals to simulate omissions and distortions in perception by the deaf are useful analytical tools. These models can help in determining the degree to which the represented loss and/or distortion of acoustic speech cues, isolated from' any central pathology, affects speech intelligibility. They can also help in evaluating the potential effectiveness of different modes of compensatory signal processing. Three examples of such models, designed on the basis of measured characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 3 publications
1
12
0
Order By: Relevance
“…It is possible that magnified masker fluctuations due to enhanced envelope coding could be a distraction that would reduce speech intelligibility. This idea is consistent with simulations of the effects of loudness recruitment with normal-hearing listeners, which showed that amplitude expansion reduced speech intelligibility, particularly in fluctuating background noises (Villchur 1977;Moore and Glasberg 1993;Moore et al 1995). Enhanced envelope coding is also likely to contribute to reduced ability of hearing-impaired listeners to detect temporal gaps between narrowband noises (Fitzgibbons and Wightman 1982;Glasberg et al 1987;Glasberg and Moore 1992).…”
Section: Physiological Sources Of Enhanced Envelope Codingsupporting
confidence: 78%
“…It is possible that magnified masker fluctuations due to enhanced envelope coding could be a distraction that would reduce speech intelligibility. This idea is consistent with simulations of the effects of loudness recruitment with normal-hearing listeners, which showed that amplitude expansion reduced speech intelligibility, particularly in fluctuating background noises (Villchur 1977;Moore and Glasberg 1993;Moore et al 1995). Enhanced envelope coding is also likely to contribute to reduced ability of hearing-impaired listeners to detect temporal gaps between narrowband noises (Fitzgibbons and Wightman 1982;Glasberg et al 1987;Glasberg and Moore 1992).…”
Section: Physiological Sources Of Enhanced Envelope Codingsupporting
confidence: 78%
“…Provided the simulation is accurate, this makes it possible to study the effect of that aspect in isolation. This has been applied to several aspects of hearing impairment, including loudness recruitment (Villchur, 1974;Duchnowski, 1989;Glasberg and Moore, 1992) and reduced frequency selectivity (Villchur, 1977;Summers and A1-Dabbagh, 1982; Celmer and Bienvenue, 1987; Gagn6 and Erber, 1987;ter Keurs et al, 1992; Baer and Moore, 1993). This study is concerned with simulating the effect of loudness recruitment and the associated reduction in dynamic range on the ability to understand speech.…”
Section: Introductionmentioning
confidence: 97%
“…Studies using spectral smearing have demonstrated detrimental effects of reduced spectral resolution on speech recognition (e.g., Villchur, 1977;ter Keurs et al, 1992ter Keurs et al, , 1993Moore, 1993, 1994;Boothroyd et al, 1996). However, the effect on speech recognition in quiet was hardly noticeable, even for smearing that simulated auditory filters six times broader than normal Moore, 1993, 1994).…”
Section: A Spectral Resolutionmentioning
confidence: 99%